THE ROLE OF SOCIAL SCIENCE LEARNING ON STUDENT ABILITY IN DIFFERENTING NATURAL AND ARTIFICIAL APPEARANCE IN ELEMENTARY SCHOOL - Elce Purwandari; Yunita Yunita; Shella Monica; Sriyanti Sriyanti; Hartatik Hartatik (JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
The purpose of this research is to determine the role of social studies learning on students abilities in natural and artificial appearances. The method in this research is the quantitative method. The data source is the students of SD Islam Azhariyah Lubuklinggau, as many as 21 people. This research is a survey using google form media. The results of the study revealed that students were able to distinguish between natural and artificial appearances through the role of social studies learning, and 9.5% chose the yes statement. It states that all students find it helpful that social studies learning can make it easier for them to understand as well as distinguish which ones are natural and which are artificial. Students stated that social studies subjects helped increase their knowledge of natural and artificial sights. This result is in accordance with the notion that social science is all knowledge related to society that examines a set of facts, concepts and events Keywords : Social Science Learning, Student Ability, Natural and Artificial Appearance